The effect of media aids in genetic carrier screening education among patients with infertility - Gordon, Annabelle; Leonard, Anthony; Thakore, Suruchi; Peterson, Kurt; Hurley, Emily; Sax, Megan (F&S Reports (Online), 2025)
To evaluate the effect of educational videos on the utilization of preconception genetic carrier screening in patients with infertility. Survey study. New patients presenting for infertility consult with one of five providers (4 physicians and 1 nurse practitioner) from November 2021 through February 2022. Patients were assigned to the web application EngagedMD video arm or in-person counseling arm for education on preconception genetic screening. The primary study outcome was completion of genetic carrier screening. The secondary outcomes were provider rating of patient comprehension and provider-rated time demand of counseling. A total of 73 patients were enrolled: 42 in the video arm and 31 in the in-person counseling arm. The survey response rate was 100% for patients and providers. Patients assigned to the video counseling arm were significantly more likely to plan to proceed with carrier screening (78.6%) than those receiving only in-office counseling (41.9%). The odds ratio associating video arm with actual completion of screening was 5.07 (95% confidence interval, 1.84–13.96). Patients who completed EngagedMD videos were perceived by providers to have a noninferior understanding of the purpose of carrier screening compared with those who underwent standard counseling, assessed via “teach-back” method. Providers also rated that multimedia education use significantly decreased demand on appointment time. The use of patient education videos increases utilization of preconception genetic carrier screening and is an acceptable alternative to in-person provider counseling.